3D uniaxial mechanical stimulation induces tenogenic differentiation of tendon‐derived stem cells through a PI3K/AKT signaling pathway. Issue 9 (29th March 2018) - Wang, Tao; Thien, Christine; Wang, Carolyn; Ni, Ming; Gao, Junjie; Wang, Allan; Jiang, Qing; Tuan, Rocky S.; Zheng, Qiujian; Zheng, Ming H.
ABSTRACT: The tendon is a mechanosensitive tissue, but little is known about how mechanical stimulation selectively signals tenogenic differentiation and neo‐tendon formation. In this study, we compared the impact of uniaxial and biaxial mechanical loading on tendon‐derived stem cells (TDSCs). Our data show that there are variations in cell signaling and cell differentiation of mouse TDSCs in response to uniaxial and biaxial loading in monolayer culture. Whereas uniaxial loading induced TDSCs toward tenogenic and osteogenic differentiation, biaxial loading induced osteogenic, adipogenic, and chondrogenic differentiation of TDSCs. Furthermore, by applying uniaxial loading on 3‐dimensional (3D) TDSC constructs, tenogenic‐specific differentiation and neo‐tendon formation were observed, results that were replicated in human TDSCs. We also showed that uniaxial loading induced PKB (AKT) phosphorylation (pAKT), whereas biaxial loading induced pERK. Most importantly, we found that inhibition of the PI3K/AKT signaling pathway could attenuate tenogenic differentiation and tendon formation in 3D TDSC constructs subjected to uniaxial loading. Taken together, our study highlights the importance of appropriate mechanobiological stimulation in 3D cell niches on tendon‐like tissue formation and demonstrates that uniaxial mechanical loading plays an essential role in tenogenic differentiation and tendon formation by activating the PI3K/AKT signaling pathway.—Wang, T., Thien, C., Wang, C., Ni, M., Gao, J., Wang, A., Jiang, Q., Tuan, R.S., Zheng, Q., Zheng, M. H. 3D uniaxial mechanical stimulation induces tenogenic differentiation of tendon‐derived stem cells through a PI3K/AKT signaling pathway. FASEB J. 32, 4804–4814 (2018). www.fasebj.org